Tetraciclyne Resistance Eschericia coli Isolated From Broiler Chicken Meat - Anisa Rizca Putri; Enny Suswati; Laksmi Indreswari (Journal of Agromedicine and Medical Sciences, 2018)
Antibiotic resistance is a serious health problem that have ben uneffective therapy. The cause of antibiotic resistance 80% comes from food of animal origin such as Broiler Chicken. E. coli contamination in antibiotic resistant chicken has been shown to transfer genetic factors between bacteria in the human intestinal system. Almost all broiler breeders use commercial feed containing tetracycline antibiotics. The use of antibiotics in the feed mixture is one of the risk factors for resistance. The aim of this study was to get an information of antibiotic resistance E. coli which isolated from broiler meat. Identification test of E. coli used two phase, presumtive test and confirmed test. Sensitivity test for E. coli to antibiotic by disc diffusion Kirby Bauer method. This study used 6 sample of upper thigh broiler meat, the antibiotic use tetracycline. The data were analyzed descriptively. The results of this study show that from 6 isolate sample, there are 4 isolate identificated as E. coli and 2 isolate show resistance to the tetracycline antibiotic. The conclusion of this study showed resistance has occurred on 50% sample.